Conceptualising the influence of the cultural orientation of Latin Americans on consumers' choice of US brands. Issue 5 (10th August 2015) - Gaur, Sanjaya S.; Bathula, Hanoku; Diaz, Carolina Valcarcel
Abstract : Purpose: – The purpose of this study is to identify the main cultural factors that influence Latin American consumers' intentions to purchase US brands. Although culture and cultural orientation have been well researched in international business and marketing literature, there is a lack of research on the relationship between consumers' cultural orientation and their bias towards foreign and domestic products. Design/methodology/approach: – The paper reviews the extant literature with a particular emphasis on the key constructs of consumer ethnocentrism, consumer xenocentrism, conspicuous consumption and consumers' national characteristics. Based on this review, the authors propose a conceptual model showing the influence of cultural orientation on the selection of US brands in Latin America. Findings: – The review of the literature shows that previous studies support the proposition of cultural orientation and preferences for foreign versus domestic products among Latin American consumers. Accordingly, in their conceptual framework, the authors posit that consumer ethnocentrism negatively influences the selection of US brands, while xenocentrism does the opposite. Conspicuous consumption is posited as moderating the influence of consumer xenocentrism on purchase intentions of the US brands. On the other hand, national characteristics of consumers in Latin America are posited as moderating the influence of both consumer ethnocentrism and consumer xenocentrism on the selection of US brands. Practical implications: – The authors also present important theoretical and practical implications that contribute to the growing body of research on consumer acculturation and country of origin effects, providing a better interpretation of consumer behaviour in the context of international and domestic markets. Originality/value: – This study fills a significant gap in the understanding of the impact of cultural orientation and conspicuous consumption on selection of US brands in Latin America. Its conceptual framework can provide the basis for future empirical studies and also improve understanding of emerging markets.